Synthesis of Some 2-amino-4-(4’-methoxyphenyl)- 6-arylpyrimidines using Microwave-Assisted one-Pot Reaction under Solvent Free Conditions - Mai, Nguyen Thi Thanh; Huu, Nguyen The (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 3, 2016)
Abstract: A convenient and efficient synthesis of pyrimidines through one-pot three-component reaction of p -methoxyaxetophenone, substituted benzaldehyde and guanidine hydrochloride in presence of solid sodium hydroxide is reported. The structure of obtained compounds have been confirmed by the resonance spectrum method from neuclei 1 H and 13 C. Obtained 2-amino-4-(4’-methoxyphenyl)-6-arylpyrimidine derivatives show pretty good antimicrobial activity.  Keywords: One-pot, microwave-assisted, 2-aminopyrimidine, solvent-free.